(untitled) (Social Science Review, 2022)
Whether it is agenda setting, policy formulation or implementation, people’s participation at all levels of policy process, decision-making and service delivery has become the prime prerequisite in the prevailing development paradigm. Although in practice there remains huge argument regarding people’s effective involvement in the development process due to unwillingness of the supply side and inefficiency, political ignorance of the demand end, it is an undeniable fact that the government of Bangladesh in the recent past has enacted laws for all levels of local government bodies with especial focus given on the people’s participation in different phases of development process. This study aims at reconnaissance of the degree of rights and opportunity given to the general people to participate in the development process presented in the existing Local Government Acts, both in rural and urban local government tiers. The study mainly focuses on the secondary sources, exclusively on the existing Local Government Acts and ordinances. The study finds that all acts have significantly included the opportunities for local people to participate in the decision-making process. It is interesting to say that the lower the tier of local government, the higher opportunity to participate in decision making process. Social Science Review, Vol. 38(1), June 2021 Page 1-16